2018
DOI: 10.5606/tgkdc.dergisi.2018.15559
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning techniques in cardiac risk assessment

Abstract: Kartal E, Balaban ME. Machine learning techniques in cardiac risk assessment. Turk Gogus Kalp Dama 2018;26(3):394-401. Cite this article as:ÖZ Amaç: Bu çalışmada amaç; makine öğrenmesi tekniklerini ve bu tekniklerin veriden öğrenme yeteneğini kullanarak kalp ameliyatı sırasında ya da kalp ameliyatı geçirdikten kısa bir süre sonra hastanın mortalite riskini öngörebilmektir.Ça lış ma pla nı: Veri seti Acıbadem Maslak Hastanesi'nden temin edildi. European System for Cardiac Operative Risk Evaluation (EuroSCORE) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
2
Order By: Relevance
“…In a study by Kartal, mortality risk was predicted using the EuroS-CORE and the C4.5 algorithm: both the EuroSCORE and the C4.5 algorithm included age, serum creatinine, LVEF, and mean pulmonary hypertension (mPAP). 28 They used their algorithm to develop a web application for risk prediction after cardiac surgery. Castela Forte et al used machine learning to evaluate 88 perioperative variables in order to predict 5-year mortality after cardiac surgery; they observed that postoperative urea concentration, age and creatinine concentration, achieved the best predictive values across different cardiac surgery types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Kartal, mortality risk was predicted using the EuroS-CORE and the C4.5 algorithm: both the EuroSCORE and the C4.5 algorithm included age, serum creatinine, LVEF, and mean pulmonary hypertension (mPAP). 28 They used their algorithm to develop a web application for risk prediction after cardiac surgery. Castela Forte et al used machine learning to evaluate 88 perioperative variables in order to predict 5-year mortality after cardiac surgery; they observed that postoperative urea concentration, age and creatinine concentration, achieved the best predictive values across different cardiac surgery types.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Machine learning algorithms can be used to analyze data and establish risk models more accurately than traditional statistical models. 26,27 Indeed, machine learning has been used to create models that predict mortality after cardiac surgery, [28][29][30][31] as well as estimate the length of hospital stay after CABG. 32 Regardless, these models are still not specific to OPCAB.…”
Section: Introductionmentioning
confidence: 99%
“…Open chest surgery leads to large amounts of hard-to-clear sputum. [ 20 - 22 ] Post-cardiothoracic surgery ICU patients are considerably different from general patients with long-term mechanical ventilation on airway resistance. [ 20 , 21 , 23 ] The HMEs are commonly used in patients who need long-term ventilation after cardiothoracic surgery, although there is still a need to study their effects on the airway resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Os tipos de aprendizado usados por máquinas são subdivididos basicamente em duas categorias, sendo elas: aprendizado supervisionado e aprendizado não-supervisionado (DEO, 2015). A principal diferença entre os dois é a presença do atributo alvo no conjunto de dados, segundo Kartal (2018), a aprendizagem supervisionada é uma forma de aprendizado na qual recebem-se diversos dados de treinamento já com respostas e são feitas previsões para pontos diferentes daqueles já treinados anteriormente.…”
Section: Introductionunclassified
“…Aprendizagem não-supervisionada, é uma forma de aprendizado na qual não existem respostas aos dados de treinamento, de acordo com Kartal (2018).…”
Section: Introductionunclassified